A hónap: április
presenter Mihály Gaál-Kovács, citizens' militia, worsening public safety, Bavarian village seeking Hungarian contacts, portrait of a forester, Mihály Habsburg, Zolotov coctail, Russian healer, Hobo's plan to move to Piliscsaba, city clerk, elections, local meeting, asking people about Piliscsaba Television, awards Mihály Gaál-Kovács